2012
DOI: 10.1155/2012/429320
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activities ofCinnamomum cassiaConstituentsIn VitroandIn Vivo

Abstract: We have investigated the anti-inflammatory effects of Cinnamomum cassia constituents (cinnamic aldehyde, cinnamic alcohol, cinnamic acid, and coumarin) using lipopolysaccharide (LPS)-stimulated mouse macrophage (RAW264.7) and carrageenan (Carr)-induced mouse paw edema model. When RAW264.7 macrophages were treated with cinnamic aldehyde together with LPS, a significant concentration-dependent inhibition of nitric oxide (NO), tumor necrosis factor (TNF-α), and prostaglandin E2 (PGE2) levels productions were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 31 publications
9
138
0
4
Order By: Relevance
“…In addition, we found that CA treatment suppresses tumor growth in mice and vessel formation in tumors. CA reduced HIF-1a and VEGF expression in cancer cells, and it has been reported to have antioxidant and anti-inflammatory actions [19][20][21][51][52][53]. These collective findings suggest that CA could be an effective cancer therapeutic agent through its orchestrated actions on apoptosis and angiogenesis in cancer and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, we found that CA treatment suppresses tumor growth in mice and vessel formation in tumors. CA reduced HIF-1a and VEGF expression in cancer cells, and it has been reported to have antioxidant and anti-inflammatory actions [19][20][21][51][52][53]. These collective findings suggest that CA could be an effective cancer therapeutic agent through its orchestrated actions on apoptosis and angiogenesis in cancer and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 75%
“…The overproduction of pro-inflammatory cytokines can provoke deleterious consequences such as septic shock and inflammatory disease (Liao et al, 2012). AF treatment markedly decreased pro-inflammatory cytokines TNF-α and IL-6 production.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that faulty cellular antioxidant systems cause organisms to develop a series of inflammatory diseases (Liao et al 2012). It was previously reported that plasma MDA concentration was found to be increased in the cows with puerperal metritis compared to the control group, while decreases of GSH-Px and CAT activities were observed (Kizil et al 2010).…”
Section: Discussionmentioning
confidence: 96%